Association of Preeclampsia with Low Platelet Count among Pregnant Females Presenting during Third Trimester - Farhana Manzoor, Fouzia Rahat, Fakhra Ashique, Rubina Waheed, Safdar Iqbal, Arslan Saleem Chughtai, (Pakistan Journal of Medical & Health Sciences, 2022)
Methods: Study conducted in the Department of Obstetrics & Gynecology, Lahore General Hospital of Lahore during 15-5-2019 to 15-11-2019 and consented to participate were considered for the study. 35 were with preeclampsia (Cases) and 35 were without (Control). The data was entered and analyzed using SPSS 25. For categorical data analysis chi square test was used using p-value ≤0.05. 70 Women of age 18-40years, parity of 20 weeks (on LMP) Results: The study results showed that the mean age of the cases group was 29.54±6.284 years whereas the mean age of control group was 28.83±7.213 years. In the present study among cases the low platelets count was noted in 26(74.3%) patients while among control group the low platelets count was found in 17(48.6%) patients. Odds of developing preeclampsia among patients aged below or equals to 30 years was 3.97 [95% CI: 0.95-16.52] whereas among aged >30, was 3.06 [95% CI: 0.68-13.78]. The odds of developing preeclampsia among low platelet count subjects with normal BMI was 3.50 [95% CI; 0.69-17.71] Conclusion: Low platelets count was associated with preeclampsia. It was found that pregnant females with low platelet count has significantly greater odds of developing preeclampsia as compared to normal platelets count females presenting during third trimester of pregnancy.